Dietary supplementation of Bacillus sp. NP5 and dayak onion simplicia powder Eleutherine bulbosa (Mill.) Urb. for the prevention of Aeromonas hydrophila in catfish Clarias sp. - R Herman Sudrajat; Munti Yuhana; Widanarni Widanarni; Julie Ekasari; Usamah Afiff (Jurnal Akuakultur Indonesia)
Aeromonas hydrophila is the main causative agent of ulcerative disease in catfish and causes considerable economic losses to Indonesian aquaculture. This study evaluates the prebiotic activity and the effect of feed supplementation of dayak onion simplicia powder (DOSP) on the immune response and survival of catfish infected with A. hydrophila. Five doses (0.20, 0.25, 0.30, 0.35, and 0.40 g/mL) of DOSP were tested in vitro to assess the prebiotic activity score. The results showed that a dose of 0.20 g/mL gave a significantly (P<0.05) higher probiotic stimulation value than other doses. In the in vivo test, the study used a completely randomized design with five treatments, namely simplicia (DOSP 20 g/kg), probiotic (PRO, Bacillus sp. NP5 108 CFU/mL, 1% v/w), combination (PRO+DOSP), and control (positive and negative). Fish were reared for 45 days and fed three times a day. On day 46, fish from all treatments, except negative control, were infected with an A. hydrophila dose of 106 CFU/mL injected intramuscularly. The results showed that the combination treatment (PRO+DOSP) gave better total erythrocytes, hemoglobin, hematocrit, total leukocytes and phagocytosis activity than probiotics, DOSP, and control. Administering the combination (PRO+DOSP) can reduce the total number of A. hydrophila lower than the probiotic, DOSP, and control treatments. In addition, the survival rate of catfish in the combined treatment (PRO+DOSP) was significantly (P<0.05) higher than probiotics, DOSP, and control. The results of this study can be a helpful reference and application for the early prevention of A. hydrophila infection.